Learning Evaluation of Writing Descriptive Text with Think Pair Share Model in Seventh Grade Students with Introvert Personality - Masykuroh, Zummala Rizqi; Zulaeha, Ida (Universitas Negeri Semarang, 2021)
Learning to write descriptive texts which is in accordance to the 2013 curriculum and the development of the 21st century has demanded students to be more productive, creative, innovative, and affective through integrated knowledge of attitudes, skills, and knowledge. Learning to write descriptive texts cannot be separated from the personality of students, namely introvert personality. Evaluation of learning by using a learning model that is appropriate to the introvert personality type is important. The purpose of this study was to evaluate the effectiveness of writing descriptive text learning with the think pair share model in VII grade students with introvert personality. This research used one-group pretest-posttest design. The results of the research based on the paired t-test with a significance value of 0.000 showed that there was a significant difference between the results of the initial test and the final test of writing descriptive text. Significant differences were experienced by introvert students, as there was an increase in the average score of the initial test from 68.07 and the average score of the final test of 80.38.